2006
DOI: 10.1128/jvi.80.5.2463-2471.2006
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Association of the Antiviral Restriction Factor TRIM5α with Human Immunodeficiency Virus Type 1 Infection

Abstract: The innate antiviral factor TRIM5␣ restricts the replication of some retroviruses through its interaction with the viral capsid protein, leading to abortive infection. While overexpression of human TRIM5␣ results in modest restriction of human immunodeficiency virus type 1 (HIV-1), this inhibition is insufficient to block productive infection of human cells. We hypothesized that polymorphisms within TRIM5 may result in increased restriction of HIV-1 infection. We sequenced the TRIM5 gene (excluding exon 5) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
115
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(124 citation statements)
references
References 55 publications
3
115
6
Order By: Relevance
“…73 However, another study did not observe a statistically significant difference in viral set point in patients homozygous for this allele, although the trend seems visible despite a small number of individuals within the H43Y patient population analyzed. 74 Similarly neutral observations have been made for other common SNPs present within the human population, including V112F, R136Q, E238W, G249D, and H419Y. Although some of these SNPs have, in individual studies, shown some small alteration of susceptibility to HIV-1 infection, these appear to be spurious, as other studies examining the same SNP have failed to confirm the small differences observed in some individual studies.…”
Section: The Emerging Relationship Between Capsid Recognition Domainsmentioning
confidence: 81%
See 2 more Smart Citations
“…73 However, another study did not observe a statistically significant difference in viral set point in patients homozygous for this allele, although the trend seems visible despite a small number of individuals within the H43Y patient population analyzed. 74 Similarly neutral observations have been made for other common SNPs present within the human population, including V112F, R136Q, E238W, G249D, and H419Y. Although some of these SNPs have, in individual studies, shown some small alteration of susceptibility to HIV-1 infection, these appear to be spurious, as other studies examining the same SNP have failed to confirm the small differences observed in some individual studies.…”
Section: The Emerging Relationship Between Capsid Recognition Domainsmentioning
confidence: 81%
“…In humans, the majority of polymorphisms occur within the RBCC motif in regions of the protein that are not thought to be responsible for modulating TRIM5a specificity to individual retroviruses. [70][71][72]74 Conversely, almost all of the nonsynonymous SNPs identified in rhesus macaques are located in the SPRY and CC domains, [75][76][77][78] which are the regions of the protein reported to dictate the specificity of TRIM5a restriction (Fig. 2).…”
Section: The Emerging Relationship Between Capsid Recognition Domainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using these cohorts have sought associations between variation in TRIM5 and a variety of outcomes, such as (a) susceptibility/resistance to HIV-1 infection (by measuring allele frequencies in high-risk yet uninfected individuals), (b) levels of viral replication in HIV-1-infected individuals, and (c) various indicators of disease progression among HIV-1-infected individuals. Most studies have reported weak associations with at least one of these outcomes, although these independent studies did not arrive at the same conclusions (Goldschmidt et al 2006;Javanbakht et al 2006;Nakayama et al 2007;Speelmon et al 2006;van Manen et al 2008). Further work will be required to determine the source of the discrepancies, and whether these reflect true biological/genotypic differences between cohorts.…”
mentioning
confidence: 81%
“…The discovery of extensive diversity in TRIM5 between primate species begged the question of whether the locus would be polymorphic within species as well, and whether naturally occurring variants differentially affect susceptibility to retroviral infection or disease progression. Thus far, reports of extensive within-species sampling for polymorphism in TRIM5 have been limited to humans (Sawyer et al 2006), most commonly in the context of HIV/AIDS cohorts (Goldschmidt et al 2006;Javanbakht et al 2006;Nakayama et al 2007;Speelmon et al 2006;van Manen et al 2008), and two species of Old World monkey ( Fig. 5; Newman et al 2005;Wilson et al 2008a).…”
Section: Trim5 Sequence Evolutionmentioning
confidence: 99%